Organisational commitment as a mediator on the correlation between the leadership attributes, organisational culture and organisational effectiveneness in Niger State primary schools - Bagobiri, Garba; Abdullahi, Arnida; Asimiran, Soaib B.; Hamzah, Siti Raba’ah (RSIS International, 2024)
Studies reveal that, leadership and organizational culture have an indirect relationship with organizational effectiveness. However, when some variables mediate the relationship, it expresses an insignificant and negative relationship. Mediation effects of organisational commitment on the relationship between leadership attribute, organisational culture, and organisational effectiveness was determined using partial correlation in this study. The survey was carried out in Niger state primary schools, and the respondents were teachers. The study has 1,572 participants and 340 make up the sample size. The findings revealed that, with the mediation of organizational commitment; Organizational effectiveness, organisational culture, and leadership attributes all had a strong and positive relationship (r =.987, p =.01) and (r =.813, p =.01), respectively. As a result of these findings, it was recommended that headmasters be encouraged to become acquainted with those leadership attributes and understand their schools’ organizational culture in order to encourage teachers to be committed to the task at hand. This could have a positive impact on organizational effectiveness. These leadership attributes can be acquired through a variety of learning programs, such as mentoring, educational leadership certification, and many others.